A photo‐based communication intervention to promote diet‐related discussions among older adults with multi‐morbidity. Issue 2 (30th November 2022) - Jih, Jane; Nguyen, Antony; Woo, Jasmin; Tran, Wen‐Ching; Wang, Abby; Gonzales, Nikko; Fung, Jennifer; Callejas, Jackeline; Nguyen, Tung T.; Ritchie, Christine S.
Abstract: Background: Little is known about how to best communicate with older adults about dietary behaviors and related factors in complex chronic disease care. Photo‐based communication could promote efficient information exchange and activate patients to effectively communicate their lived experiences. We conducted a pilot study to assess the feasibility and acceptability of a photo‐based patient‐clinician communication intervention to promote dietary discussions in geriatric primary care. Methods: Older adult patients with 2+ concurrent chronic conditions received in‐person training on photo‐taking with a smartphone before taking photos in response to the prompt, "What aspects of your everyday life affect what you eat and how much you have to eat?" Patients then shared photos and their narratives with their primary care clinician during a clinic visit. Patients and clinicians completed separate audio‐recorded post‐visit interviews to assess perspectives on the intervention. Interview transcripts were analyzed using a thematic analysis approach. Results: Fourteen patient‐clinician dyads completed the study. All except one patient‐clinician dyad (93%) completed the intervention as trained. 93% of patients and 86% of clinicians reported that they would "definitely" or "probably" be willing to engage in a future visit with photo‐sharing. Patients and clinicians shared similar perspectives on how sharing of photos during the visit enhanced communication and information exchange about dietary practices and other health‐related factors, influenced clinical recommendations made during the visits, and strengthened the patient‐clinician relationship. Conclusion: Incorporation of a photo‐based patient‐clinician communication intervention to promote discussions regarding diet and other health‐related factors could be a patient‐centered strategy to help deliver comprehensive geriatric primary care.